2017
DOI: 10.1128/aac.01841-16
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz Is Predicted To Accumulate in Brain Tissue: an In Silico , In Vitro , and In Vivo Investigation

Abstract: Adequate concentrations of efavirenz in the central nervous system (CNS) are necessary to suppress viral replication, but high concentrations may increase the likelihood of CNS adverse drug reactions. The aim of this investigation was to evaluate the efavirenz distribution in the cerebrospinal fluid (CSF) and the brain by using a physiologically based pharmacokinetic (PBPK) simulation for comparison with rodent and human data. The efavirenz CNS distribution was calculated using a permeability-limited model on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…With only trough concentration data available, we made limited inferences on time-dependent EFV profile and performed PK/PD analyses with brain tissue exposure as a more stable model estimate. However, our predicted PK profile in these matrices (no distinction between maximum plasma concentration (C max ) and C24h) agrees with the relatively flat EFV PK profile in the CSF, 21 and brain tissue, 27 and highlights the utility of EFV C24h.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…With only trough concentration data available, we made limited inferences on time-dependent EFV profile and performed PK/PD analyses with brain tissue exposure as a more stable model estimate. However, our predicted PK profile in these matrices (no distinction between maximum plasma concentration (C max ) and C24h) agrees with the relatively flat EFV PK profile in the CSF, 21 and brain tissue, 27 and highlights the utility of EFV C24h.…”
Section: Discussionsupporting
confidence: 68%
“…The model-predicted brain tissue concentrations were 267-fold higher than CSF, 4-fold higher than plasma, and 15,000-fold higher than the proteinadjusted 90% inhibitory concentration of HIV replication (IC 90 ) of 0.22 ng/mL. 26 A 2017 physiologically based pharmacokinetic model 27 predicted that EFV accumulated in the brain tissue with a steady-state concentration of 50,000 ng/ Four of the eight macaques had EFV concentrations in the CSF that were below the limit of quantification. Their concentrations were imputed as one-half of the lower limit of quantification (0.5 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to evaluate the impact of Efavirenzbased HAART on survival, longevity, climbing ability and reproductive capacity in D. melanogaster. Medications for the treatment of HIV may cause multiple toxicities such as hepatotoxicity [6], as well as central and peripheral nervous systems inflammation [27]. Nevirapine and Efavirenz have been shown to cross the blood-brain barrier and cause significant inhibition in the activity of creatine kinase, which plays a vital role in imparting cell energy homeostasis in the brain [28].…”
Section: Discussionmentioning
confidence: 99%
“…It was also concluded that in silico studies are useful tools in the planning of bioequivalence, bioavailability and other pharmacokinetic in vivo assays. [6][7][8][9]. The goal of this study was to evaluate the usefulness of in silico studies in the planning of blood collection on bioequivalence, bioavailability and other pharmacokinetic assays.…”
Section: Effect Of Different Sampling Schedules On Results Of Bioavaimentioning
confidence: 99%